Análise da Sustentabilidade da Aquicultura em Águas de Domínio da União, no Parques Aquícolas do Reservatório do Castanhão, Estado do Ceará: Estudo de Caso. - Matias, João Felipe Nogueira (2012)
The fisheries activity already reached or exceeded the limits of sustainable maximum capture in the majority of fisheries in the world. At the same time, the consumption of fish products in world-wide level comes more increasing each time. The problem is how to increase the fish production without increasing the fisheries efforts. The solution can be aquaculture, however this activity must be carried through with social insertion, environmental responsibility, economic viability and with a good governance. In Brazil, aquaculture have been a very good developing, specially in the water reservoirs of Union domain. This work had analyzed the sustentability of aquaculture in these waters using the aquícolas parks of the reservoir of Castanhão, in the state of Ceará as a case study. For this, it was used an elaboration of a socialeconomical profile of two groups of assignees (beneficiary and controll), what it demonstrated the positive influence of the fishculture in this profile. And it was elaborated subíndexes that involves social, environmental, institucional (governance) and economic dimensions of sustentability; that had allowed the construction of the index of sustainable development of the aquaculture. It was verified that this aquaculture system in question got a result fit as of media sustentability.